Technology Adoption in Mediating the Effect of Leadership Succession on Family Business Sustainability in West Sumatra - Kamener, Dahliana; Ab. Rashid, Norasekin; Azilah Husin, Nor; Irda, Irda (KnE Social Sciences, 2022)
A family business is one that can last forever. These businesses play an important role in the world’s economy and are a driving force for the world’s industries. This study aimed to investigate the effect of leadership succession on family business sustainability, mediated by technology adoption, in family business industries in the West Sumatra province. Purposive sampling was used to recruit participants with the criteria of family businesses that had been running for more than five years and had been preparing the successor of their companies. The total sample was 231 managers or chief executive officers of family companies. The results showed that leadership succession and technology adoption affected sustainability. Furthermore, technology adoption significantly mediated the relationship between leadership succession and sustainability of family businesses in West Sumatra, Indonesia. Keywords: leadership succession, family business sustainability, technology adoption